Plugging into the energy grid - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
You will often get the best information on the use and conservation of energy from people and organisations working in your specific field of interest, such as in the manufacture of organic fertiliser, vegetable canning or refrigerated transport....